Tooth injuries: Knowledge of parents of public school students from the city of Alfenas, Minas Gerais, Brazil - Cosme-Silva, Leopoldo; Fernandes, Leandro A.; Rosselli, Eliana R.; Poi, Wilson R. [UNESP]; Martins, Natália da Silva; de Lima, Daniela C. (Wiley, 2018)
Background/Aims: The prognosis of traumatized teeth can be optimized if appropriate procedures are following at the time of the accident. The aim of this study was to evaluate the level of knowledge of students’ parents from a group of Brazilian schools regarding fracture and tooth avulsion in permanent teeth. Methods: Parents of 802 students were interviewed using a pre-tested questionnaire designed to explore how they would manage their child's dental avulsion or fracture. Results: Among the parents, 8.6% reported their child had already suffered tooth injuries. Concerning dental fracture, 49.5% considered the possibility of bonding the tooth fragment and, for dental avulsion, 65.5% considered tooth replantation. Approximately 33.5% of parents would take the child to the dental office in case of fracture or dental avulsion, and of those, 66.2% would do so immediately. Further, 69.5% (for fracture) and 70.4% (for avulsion) would do so regardless of symptoms; only 24.2% and 21.3%, respectively, would seek care only if there was pain. In case of avulsion, 22.3% of those interviewed would store the tooth in liquid, such as saline solution (17.8%), water (16.4%) and fresh milk (12.2%). Conclusion: Parents had partial and insufficient knowledge as to the proper approach to be adopted in cases of fracture and dental avulsion. Previous experience of dental trauma was not related to more appropriate behavior regarding these injuries.
Keywords: dental trauma; health education; knowledge; management; tooth injuries